An Efforts Increasing the Student Learning Concentration Using a Group Tutoring Approach Self-Management Techniques - Nurjanah, Siti; Prayogi, Fiki; Sutrisno, Joko (International Journal on Advanced Science, Education, and Religion, 2025)
This research is motivated by some students who have not been able to concentrate in learning, so that efforts are needed to improve student learning concentration by using the right techniques. The purpose of this study was to determine the effectiveness of efforts to improve student learning concentration using Self-management techniques through group guidance in class XI IPA 1 SMA Tamansiswa Teluk Betung in the 2022/2023 academic year". This research uses the Guidance and Counseling Action Research (PTBK) method which is carried out in two cycles. Based on the results of the study, it is known that the problem of learning concentration in students before obtaining group guidance services with Self-management techniques obtained 50.25% after getting group guidance services with Self-management techniques in cycle I reached 56.25% in the low to medium category. Thus it can be concluded that the Self-management technique is effective in increasing learning concentration, this is indicated by the acquisition of cycle II results implemented by researchers.